Politics and Ideology in Qur’anic Translation: A Comparative Analysis Between the Indonesian Ministry of Religious Affairs Translation and the Hilali-Khan Translation - Rosi, Fauzi Fathur; Maram, Ahmad Nabilul; Wara, Jullul; Qomariya, Nurul (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This study explores the ideological and cultural influences on the interpretation of Qur'anic verses through a comparative analysis of the Ministry of Religious Affairs (Kemenag) translation from Indonesia and the translation by Muhammad Taqi al-Din al-Hilali and Muhammad Muhsin Khan from Saudi Arabia. Focusing on theological, political, and gender themes, this study examines key verses addressing concepts such as tauhid (the oneness of God), awliyā’ (relations between Muslims and non-Muslims), and gender roles. The Kemenag translation reflects Indonesia's pluralistic and inclusive policies, promoting interfaith harmony, mutual respect, and gender equality. On the other hand, the Hilali-Khan translation adheres to a literal framework influenced by Wahhabi ideology, emphasizing theological exclusivity and traditional gender hierarchies. These differences highlight the impact of socio-political contexts on Qur'anic translation strategies and their implications for societal perceptions and theological discourse. Through a comparative textual and discourse analysis approach, this study demonstrates that inclusive and context-aware translations contribute to promoting justice, tolerance, and social cohesion. The findings underscore the need to balance theological fidelity with socio-political responsiveness to serve diverse Muslim societies.